Synthesis of new chiral α-amino acid derived 3,5-disubstituted 1,2,4-triazoles - Овдійчук, О.; Гордієнко, О.; Аро, A.; Аверлан-Петі, М.-К. (Київський національний університет імені Тараса Шевченка, 2016)
An enantio pure pyrazine-linked 3,5-disubstituted 1,2,4-triazoles, an amide bond isosteres, were synthesized by ring closure of acylated with L-α-amino acid residues N-acylamidrazone precursors. Pyrrolidine ring opening of methyl esters of (2S)-2-(imino-oxo-dihydro-6H-pyrrolo[3,4-b] (hetero)aryl)alkanoic acid bearing amino acid moiety at endo-N atom of pyrrolidine ring with Boc-protected L-Phe amino acid hydrazide was firstly shown to provide a new convenient method for preparing pyridine or pyrazine derived N-acylamidrazone intermediates in good yields. No cyclic pyrrolopyridines(pyrazines) derivatives as a result of exo-imine group substitution were found as final compounds. Pyrazine-linked 1,2,4-triazoles were successfully synthesized by thermal cyclization of N-acylamidrazone derivatives using microwave-assisted irradiation. However, pyridine-containing 1,2,4-triazoles of this type are not available from corresponding N-acylamidrazones probably due to their high thermo and solvent sensibility. Under reaction conditions they underwent decomposition followed by intramolecular cyclization giving rise starting pyrrolopyridines. (Z)/(E) isomerism of N-acylamidrazone intermediates was studied by means of NMR spectroscopy and quantum chemical calculations. It was found to be dependent on the heterocycle type. A NOE experiment for phenylalanine substituted pyridine-based N-acylamidrazone demonstrated the occurrence of Z and E rotamers due to amide-type isomerism. Theoretical calculations (B3LYP DFT with the standard 6-31G(d,p) basis set) on N-acylamidrazone isomers indicated amide bond isomerism for pyridine-linked N-acylamidrazones and C=N bond isomerism for pyrazine-linked analogues.

Енантіомерно чисті азино-зв'язані 3,5-дизаміщені 1,2,4-триазоли синтезовані термальною циклізацією при мікрохвильовому опроміненні. Розкриття піролідинового кільця гідразидом амінокислоти дає новий зручний метод одержання прекурсорів N-ациламідразонів. Ізомери останніх вивчені ЯМР-спектроскопією та комп'ютерними розрахунками.
Синтез нових хіральних α-амінокислотних похідних 3,5-дизаміщених 1,2,4-триазолів
Keywords: azines; triazole; microwave irradiation; amide isomerism; computational study.; -; азини; триазол; мікрохвильове опромінення; амідна ізомерія; комп'ютерні розрахунки.; -